Design Concept for a Future Super Proton-Proton Collider - Tang, Jingyu (Frontiers in Physics, 2022)
Following the discovery of the Higgs boson at the LHC in 2012, new large colliders are being considered and studied by the international high-energy community to explore the Higgs boson in details and to probe new physics beyond the Standard Model. In China, a two-stage circular collider project, CEPC-SPPC was proposed and is under study. The first stage, CEPC (Circular Electron Positron Collier, a so-called Higgs factory) is focused on the Higgs physics, and the second stage, SPPC (Super Proton-Proton Collider) will be an energy frontier collider and a discovery machine beyond the LHC. The two colliders will share a same tunnel of 100 km in circumference, with a goal of 250 GeV in center-of-mass for CEPC and 75 TeV for SPPC Phase-I and 125-150 TeV for the SPPC ultimate goal. This article presents the design concept of the SPPC and some study results about the key accelerator physics problems and technical issues, which include luminosity optimization, beam collimation, beam-beam effects, longitudinal beam dynamics, high-field magnets and beam screen.